Inventory of metal complexes circulating in plant fluids a reliable method based on HPLC coupled with dual elemental and high-resolution molecular mass spectrometric detection - Flis, Paulina (The New phytologist, 2016)
© 2016 The Authors. New Phytologist © 2016 New Phytologist Trust.